Comparative law in a changing world - De Cruz, Peter (Routledge-Cavendish, 2007)
Providing a comprehensive and comparative analysis of the legal approach to key areas of law within different legal systems, this book offers a blueprint for comparative legal study by evaluating the epistemological debate on comparative law and comparative legal research methods.